Trabalhador escreve literatura? Uma história do autodidatismo de Otacílio de Azevedo - Silva, Wesley Lucas Batista da (2023)
The studies that consider the popular classes as producers of literary discourse are recent and still incipient. In general, studies that take these groups as objects of analysis focus only on their representations. In recent decades, however, we have witnessed a “turn” of subaltern groups that, traditionally relegated to the margins and away from legitimized cultural practices, have their place to claim and represent in their own name. Fractions of these groups are popular workers who, despite having a significant literary production, do not receive due attention from the Critics and the Academy with regard to their literary production. From this perspective, starting from an analysis of the situation of education and the official and alternative press in Fortaleza in the last quarter of the 19th and in the first quarter of the 20th century, our research seeks to investigate, from a careful reading of Musa Risonha (1920) and Fortaleza descalça (1978), by the Ceará worker-writer Otacílio de Azevedo, how the issue and representation of work and the worker appear intertwined in the author's poetry, that is, how he elaborates the issues of the world of work in the composition of his verses. In addition, we will investigate how Otacílio's case is not isolated in History, since there are considerable examples throughout the centuries in which we see workers reading and writing. Based on the analysis of these works, in dialogue with theoretical assumptions, this dissertation seeks to formulate a history of Otacílio de Azevedo's self-education and contribute with questions for the understanding of the relationship between work and writing in Brazilian literature, as well as for the discussion about the importance of literature as a form of expression of workers' experiences.